Banks' exposure to interest rate risk and the transmission of monetary policy - Matthieu Gomez; Augustin Landier; David Sraer; David Thesmar (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
We show that the cash-flow exposure of banks to interest rate risk, or income gap, affects the transmission of monetary policy shocks to bank lending and real activity. We first use a large panel of U.S. banks to show that the sensitivity of bank profits to interest rates increases significantly with measured income gap, even when banks use interest rate derivatives. We then document that, in the cross-section of banks, income gap predicts the sensitivity of bank lending to interest rates. The effect of income gap is larger or similar in magnitudes to that of previously identified factors, such as leverage, bank size or even asset liquidity. To alleviate the concern that this result is driven by the endogenous matching of banks and firms, we use loan-level data and compare the supply of credit to the same firm by banks with different income gap. This analysis allows us to trace the impact of banks' income gap on firm borrowing capacity, investment and employment, which we find to be significant.
Keywords: E52; G21; E44; 330; Interest rate risk; monetary policy; bank lending